Innovative Floating Latrine Technology Solutions for Regions Island Sinjai Regency, South Sulawesi Province, Indonesia - Muh. Saleh; Ain Khaer; Muhammad Zul Bashar; Anwar Daud (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Ownership of toilets has long been an environmental sanitation problem in the coastal areas of Sembilan Island which are generally inhabited by residents with improper domestic wastewater (black water) treatment. Most of the people in the area use a “slung” type of toilet in their house, which results in direct contacts of their domestic wastewater, such as black water or feces, with nearby bodies of water. Additionally, these coastal communities openly defecate in the seafront at night. The implementation of community service is carried out in 4 stages, namely: socialization of innovative technology and FGDs, workshops, training in making innovative floating latrine technology, and assistance in installing floating/tidal latrines. The socialization was carried out at the sub-district level by inviting residents and related stakeholders, which was then followed by FGDs to explore problems and find solutions to sanitation-related issues. The workshop was conducted by making a manual for the management of floating/tidal latrines. The training on making floating/tidal latrine technology is only for the residents of Pulau Sembilan. Lastly, assistance was provided for the installation of floating latrines in a predetermined location. This community service resulted in the development of innovative floating / tidal latrine technologies that meet sanitation standards, making it easier for residents of Pulau Sembilan to defecate without violating health and hygiene standards. This technology has also been successfully developed and implemented at a relatively affordable cost with the hope that this innovation can be easily duplicated by other communities in Pulau Sembilan.